Overexpression of lipA or glpD_RuBisCO in the Synechocystis sp. PCC 6803 Mutant Lacking the Aas Gene Enhances Free Fatty-Acid Secretion and Intracellular Lipid Accumulation - Kamonchanock Eungrasamee (MDPI AG, 2021)
Although engineered cyanobacteria for the production of lipids and fatty acids (FAs) are intelligently used as sustainable biofuel resources, intracellularly overproduced FAs disturb cellular homeostasis and eventually generate lethal toxicity. In order to improve their production by enhancing FFAs secretion into a medium, we constructed three engineered Synechocystis 6803 strains including KA (a mutant lacking the aas gene), KAOL (KA overexpressing lipA, encoding lipase A in membrane lipid hydrolysis), and KAOGR (KA overexpressing quadruple glpD/rbcLXS, related to the CBB cycle). Certain contents of intracellular lipids and secreted FFAs of all engineered strains were higher than those of the wild type. Remarkably, the KAOL strain attained the highest level of secreted FFAs by about 21.9%w/DCW at day 5 of normal BG11 cultivation, with a higher growth rate and shorter doubling time. TEM images provided crucial evidence on the morphological changes of the KAOL strain, which accumulated abundant droplets on regions of thylakoid membranes throughout the cell when compared with wild type. On the other hand, BG11-N condition significantly induced contents of both intracellular lipids and secreted FFAs of the KAOL strain up to 37.2 and 24.5%w/DCW, respectively, within 5 days. Then, for the first time, we shone a spotlight onto the overexpression of lipA in the aas mutant of Synechocystis as another potential strategy to achieve higher FFAs secretion with sustainable growth.